Persamaan eksponen

  1. Jika  x{}^{1/2}+ x{}^{-1/2}= 2 maka tentukan nilai dari x{}^2+ x{}^{-2}
    Penyelesaian :
    x{}^{1/2}+ x{}^{-~1/2}= 2
    (x{}^{1/2}+ x{}^{-~1/2}){}^2= 2{}^2
    x + 2 + x{}^{-1}= 4
    x + x{}^{-1}= 4 – 2
    (x + x{}^{-1}){}^2= 2{}^2
    x{}^2 + 2 + x{}^{-2}= 4
    x{}^2 + x{}^{-2}= 2

  2. Jika f(x)= a{}^x+ a{}^{-~x} dan g(x)= a{}^x– a{}^{-~x}
    maka tentukanlah :
    a. (f(x)){}^2– (g(x)){}^2
    b. g(2x) – f(x).g(x)
    Penyelesaian :
    a). (f(x)){}^2– (g(x)){}^2 = (a{}^x+ a{}^{-~x}){}^2– (a{}^x– a{}^{-~x}){}^2
      (f(x)){}^2– (g(x)){}^2 = (a{}^{2x} + 2 + a{}^{-~2x}) – (a{}^{2x} – 2 + a{}^{-~2x})
      (f(x)){}^2– (g(x)){}^2 = a{}^{2x} + 2 + a{}^{-~2x} – a{}^{2x} + 2 – a{}^{-~2x}
      (f(x)){}^2– (g(x)){}^2 = 4

    b). g(2x) – f(x).g(x) = a{}^{2x}– a{}^{~-2x}– (a{}^x+ a{}^{-x})(a{}^x– a{}^{-x})
      g(2x) – f(x).g(x)= a{}^{2x}– a{}^{-2x}– (a{}^{2x}– a{}^{-2x})
      g(2x) – f(x).g(x)= a{}^{2x} – a{}^{~-2x} – a{}^{2x} + a{}^{~-2x} = 0


  3. Jika x = (1 + {1/n}){}^n dan y = (1 + {1/n}){}^{n+1} maka tunjukkanlah bahwa y{}^x = x{}^y

    nomor 3